2010
DOI: 10.2355/isijinternational.50.1622
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Slag Eye Area in Argon Stirred Ladles

Abstract: Fig. 1. A schematic of ladle gas injection operation illustrating the formation of slag eye.ture water model in the presence of different upper phase liquids as a function of gas flow rate, bath depth, and thickness of the overlying liquid. The authors also critically reviewed previous studies [1][2][3] and went on to show that available correlations on slag eye area are largely inadequate to describe their experimental results. Based on the principles of momentum conservation, a fresh analysis of the subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 13 publications
0
40
0
1
Order By: Relevance
“…Then they proposed a new model for the slag eye, 11) which is an extension to the previous one, where the eye size was computed from the primary operating variables of the ladle and demonstrated reliable predictive abilities in a variety of multi-phase systems. Peranandhanthan and Mazumdar 12) developed a new polynomial correlation for slag eye area, in which the dimensionless slag eye area can be expressed in terms of Froude number, density ratio, and Reynolds number. Recently, Krishnapisharody and Irons 13) proposed a new model for slag eyes in the ladles covered with thick slag, indicating that the eyes formed can be smaller than the spout region when the slag layer is sufficiently thick.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…Then they proposed a new model for the slag eye, 11) which is an extension to the previous one, where the eye size was computed from the primary operating variables of the ladle and demonstrated reliable predictive abilities in a variety of multi-phase systems. Peranandhanthan and Mazumdar 12) developed a new polynomial correlation for slag eye area, in which the dimensionless slag eye area can be expressed in terms of Froude number, density ratio, and Reynolds number. Recently, Krishnapisharody and Irons 13) proposed a new model for slag eyes in the ladles covered with thick slag, indicating that the eyes formed can be smaller than the spout region when the slag layer is sufficiently thick.…”
Section: Modeling Of Gas-steel-slag Three-phase Flow In Ladle Metallumentioning
confidence: 99%
“…The % error was calculated according to the following formula: It is seen from Table 1 that the percentage errors in the estimated slag 'eye' radius range from 75.27% to 99.33% which are huge. The percentage errors in the radius obtained from other researchers 7,9,11,12) which had different operating slag height to bath height ratios were even larger and hence, are not shown here. This clearly proves the fact that the correlations developed to predict the open 'eye' area in laldes can not be used for tundishes.…”
Section: Resultsmentioning
confidence: 96%
“…On comparing the present water model results with the estimates obtained from the correlations for ladles, 2,3,7,9,11,12,15) it can be concluded that the mechanism of slag 'eye' formation in a tundish is different from that in ladles, and hence, a new correlation needs to be developed for predicting the size of slag 'eye' in a tundish.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Plume eye Spout eye [56][57][58][59][60][61][62][63][64][65][66][67] Spitting Splash Reverseemulsification [56][57][58][59][60][61][62][63][64][65][66][67] 3. 底吹き単孔ノズルによる気泡の生成ならびに それに伴う液滴の発生 3・1 単孔ノズルによる気泡の生成挙動 11,16,[19][20][21][22][23][24][25][26][27] Sano and Mori 4,6 Fig …”
Section: Gas-lift Effectunclassified